2017
DOI: 10.1002/cne.24338
|View full text |Cite
|
Sign up to set email alerts
|

CNS synapses are stabilized trans‐synaptically by laminins and laminin‐interacting proteins

Abstract: The retina expresses several laminins in the outer plexiform layer (OPL), where they may provide an extracellular scaffold for synapse stabilization. Mice with a targeted deletion of the laminin β2 gene (Lamb2) exhibit retinal disruptions: photoreceptor synapses in the OPL are disorganized and the retinal physiological response is attenuated. We hypothesize that laminins are required for proper trans-synaptic alignment. To test this, we compared the distribution, expression, association and modification of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…The observed changes in the adhesive behavior of RPCs were evaluated in relation to expression of a panel of cell surface adhesion molecules known to serve as receptors for one or more of the ECM materials used as substrates in this study: integrin α3, integrin α7, integrin β3, and CD44. As noted in Table 4 , integrin α3 60 65 and integrin α7 66 69 bind to FN and LM, CD44 39, 75 78 is the receptor for HA, and integrin β3 70 74 is expressed by cells of the retinal pigment epithelium (RPE) and highly implicated in retinal angiogenesis. We observed that RPCs seeded onto substrates identified as ligands expressed somewhat higher levels of most receptors than when seeded onto PLL.…”
Section: Resultsmentioning
confidence: 99%
“…The observed changes in the adhesive behavior of RPCs were evaluated in relation to expression of a panel of cell surface adhesion molecules known to serve as receptors for one or more of the ECM materials used as substrates in this study: integrin α3, integrin α7, integrin β3, and CD44. As noted in Table 4 , integrin α3 60 65 and integrin α7 66 69 bind to FN and LM, CD44 39, 75 78 is the receptor for HA, and integrin β3 70 74 is expressed by cells of the retinal pigment epithelium (RPE) and highly implicated in retinal angiogenesis. We observed that RPCs seeded onto substrates identified as ligands expressed somewhat higher levels of most receptors than when seeded onto PLL.…”
Section: Resultsmentioning
confidence: 99%
“…However, deletion of RIBEYE, which substantially decreases the number of ribbons in retinal synapses and disrupts neurotransmitter release, does not affect the overall organization and synaptic connectivity of the retina (49). The loss of the typical triad organization does not disturb the gross structure of bipolar dendritic tips, including mGluR6 accumulation (5052). Together with findings from the present report, perturbations in synaptic inputs and integrity did not directly lead to mGluR6 elimination via degradation, suggesting that synapse loss might have resulted from phagocytosis by microglia cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the KVR motif does not appear to be conserved in neurexins (Figure 10), thus other factors could be involved. The fine regulation of the affinities between DG and these neuronal proteins may make important contributions in the central nervous system for the stability of synaptic elements (Hunter et al, 2017) and/or for neuronal pathfinding (Wright et al, 2012).…”
Section: Is Affinity Regulated By Modularity?mentioning
confidence: 99%